Effects of Flooding and Endogenous Hormone on the Formation of Knee Roots in Taxodium ascendens - Qian, Zhuangzhuang; Wu, Lin; Tang, Luozhong (Frontiers in Plant Science, 2022)
Taxodium ascendens is a typical tree species with high flood tolerance, and it can generate knee roots in the wetlands. In this study, the number and size of knee roots and soil flooding conditions were investigated. Furthermore, physiology, biochemical responses, and the anatomical structure of knee roots and underground roots were measured at different developmental stages. This study aimed to understand the adaptation mechanism of T. ascendens to flooding stress and the formation mechanism of the knee roots. The results showed that the formation of knee roots was significantly affected by the soil water table (P < 0.05), the middle water table was more conducive to the formation of knee roots. In the middle water table, the 1-aminocyclopropane-1-carboxylic acid (ACC) content and ACC synthase activity were significantly lower in the knee roots than in the underground roots. The knee roots at the young-aged stage showed the highest ACC oxidase activity among the development stages of the knee roots. The ethylene release rate was significantly higher in the knee roots than in the underground roots (P < 0.05). Indole-3-acetic acid (IAA) content first increased and then decreased with knee root development. The cells of the periderm at the apex of the knee roots were dead and had a large number of intercellular spaces, which was beneficial for the growth of T. ascendens. In conclusion, the middle water table induced the production of endogenous hormones and the formation of knee roots, which improved roots ventilation and flooding tolerance of T. ascendens. The results obtained can gain a basis for the adaption and formation mechanism of knee roots and provide scientific evidence for the afforestation and management under wetland conditions.